Impacts of Sustainability Performance and Firm Characteristics on Risk and Corporate Value - Lilik Handajani; Lalu Hamdani Husnan; Endar Pituringsih (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThis research investigates the effect of sustainability performance and firm characteristics on risk and corporate value by applying a structural equation model. The focus of the analysis is on Indonesian companies that received sustainability ratings continuously from the Asia Sustainability Reporting Award during the 2018-2019 period. The process involved analyzing secondary data presented in annual and sustainability reports to obtain relevant content for corporate sustainability performance. The findings showed that the improvement of the sustainability performance was able to significantly reduce corporate risk but did not have any influence on corporate value. It was also discovered that large companies with political connections face increased risk, thereby, limiting their ability to enhance corporate value significantly. Moreover, the incorporation of sustainability investment strategies was observed to require business risk management to reduce future environmental and social risks associated with long-term corporate value creation. Keywords:sustainability performance, risk, firm value Dampak Kinerja Keberlanjutan dan Karakteristik Perusahaan Terhadap Risiko dan Nilai Perusahaan AbstrakPenelitian ini mengkaji pengaruh kinerja keberlanjutan dan karakteristik perusahaan terhadap risiko dan nilai perusahaan. Analisis model struktural digunakan untuk menguji perusahaan Indonesia yang secara konsisten menerima peringkat keberlanjutan dari Asia Sustainability Reporting Award pada tahun 2018-2019. Data sekunder berupa laporan tahunan dan laporan keberlanjutan perusahaan dianalisis untuk memperoleh konten yang relevan dengan kinerja keberlanjutan perusahaan. Hasil penelitian menunjukkan bahwa peningkatan kinerja keberlanjutan akan menurunkan risiko perusahaan secara signifikan, namun tidak mempengaruhi peningkatan nilai perusahaan. Perusahaan besar dengan koneksi politik dapat menghadapi peningkatan risiko, namun tidak dapat berkontribusi secara signifikan untuk peningkatan nilai perusahaan. Penggabungan strategi investasi keberlanjutan membutuhkan manajemen risiko bisnis untuk mengurangi risiko lingkungan dan sosial di masa depan untuk penciptaan nilai perusahaan dalam jangka panjang. Kata kunci:kinerja keberlanjutan; risiko, nilai perusahaan